The Effect of Leverage, Profitability, Liquidity Ratio, and Inflation towards Financial Distress: Study From the Manufacturing Industry in Indonesia - Everaldi Oktavian; Sarwo Handoyo (International Journal of Management Science and Application, 2023)
Research on financial distress is an important component in the assessment of internal and external parties of the company to see whether the company’s financial condition is in a good position or is in a bad position. This is important for internal parties in the process of reviewing the company’s financial condition to carry out decision-making to improve or enhance the company’s financial capabilities. This is also important for external parties in the decision-making process in determining whether the company is worth investing in. This study aims to analyze the effect of financial ratios in the form of leverage, profitability, and liquidity ratios along with inflation on financial distress in manufacturing companies listed on the Indonesia Stock Exchange. This study used panel data regression with a purposive sampling method with a total of 103 samples. Data processing in this study uses Eviews 9. The results of this study indicate that there is a positive influence between profitability and liquidity on financial distress indicator. As for other variables, leverage has a negative effect on financial distress indicator and inflation has no effect on financial distress indicator. This research can contribute to investors and company management in carrying out the decision making process by paying attention to the company's financial ratios and inflation in Indonesia and also contribute to developing knowledge in the field of finance study as it enhance the causality of financial distress. Suggestions that can be given for further research are to use other independent variables in the form of corporate governance and corporate social responsibility disclosure which may show results that better reflect the company’s qualitative capabilities.